2021
DOI: 10.3390/ijerph18084167
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Environmental Determinants Relevant to Health and Wellbeing in Remote Australian Indigenous Communities: A Scoping Review of Grey Literature

Abstract: The high prevalence of preventable infectious and chronic diseases in Australian Indigenous populations is a major public health concern. Existing research has rarely examined the role of built and socio-political environmental factors relating to remote Indigenous health and wellbeing. This research identified built and socio-political environmental indicators from publicly available grey literature documents locally-relevant to remote Indigenous communities in the Northern Territory (NT), Australia. Existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…These standards capture features of environments such as housing, public sanitation facilities, water supply, power supply, sewerage systems, rubbish collection and disposal, repair and maintenance of environmental health infrastructure. Systematically selected built environmental indicators generated in the scoping review [ 43 ], followed by this concept mapping study, may support the environmental and public health sectors to identify priority indicators that can be actioned in the shorter term (e.g., within the next 2–3 years) and the longer term (within 5–10 years). The most important built environmental indicators identified in this research may provide an evidence base for the NT Department of Health to influence the broader government system through networking, communicating, and negotiating (on behalf of the community) with regional councils and other sections in the government system to address local-level environmental health issues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These standards capture features of environments such as housing, public sanitation facilities, water supply, power supply, sewerage systems, rubbish collection and disposal, repair and maintenance of environmental health infrastructure. Systematically selected built environmental indicators generated in the scoping review [ 43 ], followed by this concept mapping study, may support the environmental and public health sectors to identify priority indicators that can be actioned in the shorter term (e.g., within the next 2–3 years) and the longer term (within 5–10 years). The most important built environmental indicators identified in this research may provide an evidence base for the NT Department of Health to influence the broader government system through networking, communicating, and negotiating (on behalf of the community) with regional councils and other sections in the government system to address local-level environmental health issues.…”
Section: Discussionmentioning
confidence: 99%
“…The brainstorming component of the concept mapping study identified locally relevant built environmental indicators from a scoping review of community and strategic planning documents [ 43 ] with evidence of Indigenous input [ 75 ]. In our discussions, stakeholders identified several policy and strategic planning documents developed through community consultation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations